2021
DOI: 10.1021/acs.inorgchem.1c03431
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Various One-Dimensional ZnS/MnS Heteronanostructures with Varied Diameters via the Multistep Solution–Solid–Solid Growth Method

Abstract: A series of novel one-dimensional (1D) ZnS/MnS heteronanostructures were prepared by a multistep solution–solid–solid (SSS) growth method using [(C4H9)2NCS2]2Zn and [(C4H9)2NCS2]2Mn as the precursors and Ag2S as the catalyst. The composition of the 1D heteronanostructures could be effectively modulated by varying the addition sequence of the precursors, such as the Ag2S/MnS/ZnS and Ag2S/ZnS/MnS heteronanostructures, which were obtained through the successive addition of [(C4H9)2NCS2]2Zn and [(C4H9)2NCS2]2Mn pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Their unique properties, such as high aspect ratio, large surface-to-volume ratio, and quantum confinement effects, have made nanowires indispensable for diverse technological advancements [ 6 , 7 ]. The influence of nanowire size at the nanoscale level induces substantial changes in optical and electronic properties, leading to notable alterations in bandgap and electrical characteristics [ 8 , 9 ]. Consequently, precise control over material phase composition and phase transition processes during nanowire synthesis significantly influences their structural, electronic, and mechanical attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Their unique properties, such as high aspect ratio, large surface-to-volume ratio, and quantum confinement effects, have made nanowires indispensable for diverse technological advancements [ 6 , 7 ]. The influence of nanowire size at the nanoscale level induces substantial changes in optical and electronic properties, leading to notable alterations in bandgap and electrical characteristics [ 8 , 9 ]. Consequently, precise control over material phase composition and phase transition processes during nanowire synthesis significantly influences their structural, electronic, and mechanical attributes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] Additionally, it was reported that the metal‐dithiocarbamate complex had sufficiently high reactivity to produce metal sulfides. [ 9,22–26 ]…”
Section: Introductionmentioning
confidence: 99%
“…[17] Additionally, it was reported that the metal-dithiocarbamate complex had sufficiently high reactivity to produce metal sulfides. [9,[22][23][24][25][26] Based on the above considerations, here, the luminescent AgInS 2 @In 2 S 3 core@shell nanoparticles were fabricated via the reaction of preformed Ag…”
Section: Introductionmentioning
confidence: 99%